Early Allograft Dysfunction After Liver Transplantation With Donation After Circulatory Death and Brain Death Grafts: Does the Donor Type Matter?. Issue 8 (August 2021) - Mazilescu, Laura Ioana; Kotha, Sreelakshmi; Ghanekar, Anand; Lilly, Leslie; Reichman, Trevor W.; Galvin, Zita; Cattral, Mark S.; Bhat, Mamatha; McGilvray, Ian D.; Sapisochin, Gonzalo; Sayed, Blayne; Selzner, Markus; et al.
Abstract : Background: Early allograft dysfunction (EAD) after liver transplantation has been associated with long-term reduced graft and patient survival. Methods: In this single-center cohort study, we aimed to compare incidence, risk factors, and outcomes in liver transplant recipients who developed EAD. Patients who received donation after circulatory death (DCD) or donation after brain death (DBD) grafts between January 2007 and December 2017 were included. EAD was defined as bilirubin of ≥10 mg/dL (171 μmol/L) or an international normalized ratio of ≥1.6 on postoperative day 7 or transaminases >2000 UŁ in the first-week posttransplantation as previously described. Results: In our cohort of 1068 patients, incidence of EAD was 44%. EAD occurred more frequently in the DCD versus DBD group (71% versus 41%, P < 0.01). Overall, recipients who developed EAD showed a significantly lower graft and patient survival at 1, 3, and 5 y after transplantation (all P < 0.05). This was also the case for recipients of DBD grafts. However, for recipients of DCD grafts, patient and graft survival were not affected by the presence of EAD. For recipients of DBD grafts, donor age, body mass index (BMI) and gender, recipient BMI and model for end-stage liver disease score and warm and cold ischemia time were associated with EAD. For DCD recipients, donor BMI and cold ischemia time were associated with EAD. Conclusions: In our cohort study, EAD resulted in reduced long-term patient and graft survival only for DBD recipients but not for DCD recipients. Predictive markers for EAD were dependent on the donor type.